Trombone Studies in Contemporary Music - NAGEL, Robert (Belwin Mills)
Buku ini memuat 14 lagu untuk instrumen trombone, yaitu:- Intervals- Odd Meter 'Pop'- Dynamic Contrasts- Pentatonic Syncopation- Impressionism- Quartal Melody- Dodecaphonic (12 tone)- Pointillistic- Special Effects- Spatial Notation- Aleatory Music- Combined Techniques- Changing Meters- Complex Rhytm